Functional identification of the promoter of SLC4A5, a gene associated with cardiovascular and metabolic phenotypes in the HERITAGE Family Study - Stütz, Adrian M (Nature Publishing Group, 2009)
The sodium bicarbonate cotransporter gene SLC4A5, associated earlier with cardiovascular phenotypes, was tested for associations in the HERITAGE Family Study, and possible mechanisms were investigated. Twelve tag-single nucleotide polymorphisms (SNPs) covering the SLC4A5 gene were analyzed in 276 Black and 503 White healthy, sedentary subjects. Associations were tested using a variance components-based (QTDT) method with data adjusted for age, sex and body size. In Whites, rs6731545 and rs7571842 were significantly associated with resting and submaximal exercise pulse pressure (PP) (0.0004 <P<0.0007 and 0.002<P<0.003 respectively). Additionally, rs6731545 was associated with submaximal-exercise systolic blood pressure (SBP) and rate pressure product (P=0.002, both). New associations between rs6731545 and submaximal-exercise VO(2) (P=0.003), rs7587117 and rs7571842 and VCO(2) (0.0005<P<0.0009) and rs828853 and VE (P=0.002) were found. All these associations had a FDR<0.05. Single-marker associations were confirmed in haplotype analyses. Using in silico analysis, evidence was found for a main and an alternative promoter for SLC4A5. Specific promoter activity was experimentally confirmed using reporter constructs targeting both promoters in three physiologically relevant cell lines. Re-sequencing of 32 individuals having opposite homozygotes for rs7571842 and rs6731545 and exhibiting significantly different phenotypes showed no SNPs in the alternative promoter and no differences between the groups with SNPs in the main promoter. Also, of all known SLC4A5-coding SNPs, only one synonymous SNP was detected. Summarizing, the observed associations with resting and submaximal-exercise cardiovascular and metabolic traits in the HERITAGE Family Study are likely due to neither variation in the promoter nor known coding SNPs of SLC4A5.